Analisis Potensi Lokal sebagai Sumber Belajar Berbasis Laboratorium Lapangan dalam Pembelajaran Geografi (Studi kasus Objek wisata Alam Bantimurung, Desa Jenetaesa, Kecamatan Simbang, Kabupaten Maros, Provinsi Sulawesi Selatan) - Shahabi, Shaiful; Umar, Ramli; H, Hasriyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In geography learning, it is closely related to nature, so the need for learning resources based on field laboratories is very much needed. The ideal implementation of learning should be carried out outside the classroom by utilizing the environment as a learning object in identifying and analyzing natural phenomena. However, there are difficulties for educators in implementing learning outside the classroom due to the lack of facilities and infrastructure, as well as location knowledge that is relevant to geography learning materials. This study is intended to analyze the utilization of the potential of the Bantimurung Natural Tourism Area, Jene Taesa Village, Simbang District, Maros Regency as a learning resource based on field laboratories in geography learning. This type of research is descriptive qualitative with triangulation methods, namely observation, interviews and documentation studies. With very complex natural phenomena, the results of this study indicate that the Bantimurung Natural Tourism Area, Jene Taesa Village, Simbang District, Maros Regency. Has great potential to be used as a source of field learning for geography learning that can be utilized by teachers and students in supporting geography learning.